Analisis Pengaruh Kompetensi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Penanggulangan Bencana Daerah Kabupaten Alor - Yurni Hanaou (Jurnal Ilmiah Wahana Pendidikan, 2023)
Employee performance is the result of work achieved by employees in carrying out the tasks assigned to them based on skills, experience, and sincerity as well as time from employees. This study aims to determine the effect of competency on employee performance either partially or simultaneously. This research was conducted on civil servants at the Regional Disaster Management Agency Office of Alor Regency, totaling 26 people. Retrieval using saturated sampling techniques so that the entire population is used as a sample. Data collection used observation, interviews, questionnaires, and literature study while data analysis techniques used descriptive statistics, research instrument tests consisting of validity and reliability tests, classic assumption tests consisting of normality tests, heteroscedasticity tests, multicollinearity tests, and linearity tests then for determine the effect of independent variables on the dependent variable used partial test and simultaneous test. The results showed that both partially and simultaneously all the variables in this study namely competence, work discipline, and work environment affect employee performance variables which are indicated by the significance value of the t-test for each variable of 0.005, 0.039, and 0.041 and the significance value of the F test is 0.001, where the significance value of the t-test (sig) for each variable and the significance value of the F test is smaller than the alpha value used (0.05)..